2019
DOI: 10.1111/inm.12576
|View full text |Cite
|
Sign up to set email alerts
|

‘It was me answering my own questions’: Experiences of method of levels therapy amongst people with first‐episode psychosis

Abstract: In this study, we aimed to understand how people with first‐episode psychosis experienced a transdiagnostic cognitive therapy called method of levels (MOL). Semistructured interviews were conducted with 12 individuals who were participants of a feasibility randomized controlled trial of MOL for first‐episode psychosis. Interviews were analysed using thematic analysis. Four superordinate themes were identified: ‘The therapist's approach’; ‘I was in control’; ‘Thinking and talking’; and ‘Looking at problems from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 49 publications
1
17
0
2
Order By: Relevance
“…Method of Levels has been successfully used with adults experiencing psychological distress in a variety of settings (Carey & Mullan, , ; Carey & Spratt, ). A recent qualitative study exploring how individuals with first‐episode psychosis experience MOL found that therapy was perceived most helpful when individuals had control over the therapeutic process which gave them the opportunity to explore difficulties and generate new solutions (Griffiths et al, ). However, no studies with young people have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Method of Levels has been successfully used with adults experiencing psychological distress in a variety of settings (Carey & Mullan, , ; Carey & Spratt, ). A recent qualitative study exploring how individuals with first‐episode psychosis experience MOL found that therapy was perceived most helpful when individuals had control over the therapeutic process which gave them the opportunity to explore difficulties and generate new solutions (Griffiths et al, ). However, no studies with young people have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…None of the participants in the MOL group reported that they stopped attending therapy because it was not meeting their needs, which suggests the intervention is acceptable to people experiencing FEP. This is supported by data collected using the Session Rating Scale (Duncan et al, ) and the findings of the nested qualitative study (Griffiths et al, ). Having control over therapy, being able to speak openly about problems, and having the opportunity to develop new perspectives were particularly valued by participants receiving MOL.…”
Section: Discussionmentioning
confidence: 61%
“…A nested qualitative study was also undertaken to investigate participants’ experiences of trial participation, the MOL intervention, and the service user‐led appointment booking system. The results of this qualitative study have been reported separately (Griffiths et al, ). The trial was prospectively registered with the ISRCTN registry (ISRCTN13359355).…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…One successful example of a way to enhance control is to provide patients with the opportunity to determine the timing, appointment scheduling, session length, and duration of their psychological therapy (38). Further successful examples include providing people with the control of the topic of each therapy session (39), or providing them with technology to exert moment-by-moment control of their level of exposure during therapy (40).…”
Section: The Core Principles Of Pct Involved In Psychological Distresmentioning
confidence: 99%